PENGARUH KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN FISKUS DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA BITUNG - Tulenan, Rudolof A.; Sondakh, Jullie J.; Pinatik, Sherly (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Taxes have been becoming one of many issues dealt in a country. One of the countryâs incomes comes from taxes, without societies there will be no taxes. Taxes could be defines as a collection done by the government in the purpose of creating a prosperous society, based on the written law about collections, government does not given immediate contraception to the taxers. This research was done in Bitung City, that aim to explain about effect ofÂ taxpayer the awareness , the quality of tax authorities services and taxes punishment for the obedience of an individual must pay. This research used quantitative research with 100 samples taken from all taxpayer population at KPP Pratama Bitung. The researchâs method used in this research is double linear regression, data qualities test, classic assumptions test, hypothesis testing (subject t and subject F). This researchâs method uses a SPSS software version 23. The hypothesis researchâs result partially (subject t) awareness of taxpayer, tcount = 5.045 and ttable = 1.984 so Ha1 get accepted then the awareness of taxpayer impacting the must pay obedience. Tax authorities service, tcount = 1.587 and ttable = 1.984 so Ha2 denied then the tax authorities service does not impacting the taxpayer obedience. Taxes punishment tcount = 1.554 and ttable = 1.984 so Ha3 denied than the tax authorities punishment does not impacting the taxpayer obedience.Keywords : Awareness of taxpayer, Quality of Tax Authorities and Tax Punishment towards the Obedience of Taxpayer Personally.